Selenium-sulfur co-doped asphalt-based hard carbon material as well as preparation method and application thereof

CN119637850AActive Publication Date: 2025-03-18SHANGHAI SHANSHAN NEW MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411972246.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-18
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The energy density increase of existing lithium-ion batteries is approaching the theoretical limit, and lithium dendrites are easily formed during fast charging or circulation, and the charging efficiency is low; at the same time, asphalt is easily graphitized during heat treatment, resulting in the low specific capacity of the prepared carbon material.

Method used

Using selenium-sulfur co-doped asphalt-based hard carbon material, a negative electrode material with high lithium storage capacity and good electrochemical properties is prepared by mixing the asphalt, selenium source and sulfur source in a specific proportion and carbonized.

Benefits of technology

It has achieved a high lithium storage capacity, 343-380mAh/g, and has good electrochemical properties. It is suitable for the negative electrode material of lithium-ion batteries. The preparation method is simple, economical and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119637850A_ABST
    Figure CN119637850A_ABST
Patent Text Reader

Abstract

The invention discloses a selenium-sulfur co-doped asphalt-based hard carbon material as well as a preparation method and application thereof. The selenium-sulfur co-doped asphalt-based hard carbon material is prepared from the following raw materials: asphalt, a selenium source and a sulfur source. The selenium-sulfur co-doped asphalt-based hard carbon negative electrode material has relatively high lithium storage capacity; according to the preparation method, co-doping of selenium and sulfur is achieved in the carbonization process, the tendency that asphalt is prone to graphitization in the high-temperature carbonization process is inhibited, the preparation method is simple, economical and environmentally friendly, and the material is used as a lithium ion battery negative electrode material, so that a lithium ion battery has good electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery negative electrode materials, and in particular to a selenium-sulfur co-doped asphalt-based hard carbon material and a preparation method and application thereof. Background Art

[0002] With the expansion of the global population and economic prosperity, our thirst for energy is increasing day by day, while our dependence on and abuse of fossil fuels has caused serious damage to our environment. In order to meet this challenge, countries around the world are actively promoting the development and application of renewable energy such as solar energy and wind energy. However, the supply of these renewable energy sources is often unstable and discontinuous, which makes it urgent to develop efficient and cost-effective energy storage and conversion technologies. At present, lithium-ion batteries with graphite as anode have been widely used in many fields, especially in portable electronic devices, due to their excellent energy density and long cycle life. However, with the rapid development of electronic equipment and electric vehicle industries, our demand for energy is growing rapidly, which puts higher standards on energy storage systems. Although lithium-ion batteries with graphite as anode have excellent performance, their energy density is approaching the theoretical limit. The charging efficiency of graphite anode is low, and lithium dendrites are easily formed during fast charging or cycling.

[0003] Hard carbon has a series of significant advantages as anode materials for lithium-ion batteries: (1) The reversible specific capacity of hard carbon for lithium storage is relatively high, generally 500mAh / g to 700mAh / g, and can even reach more than 1000mAh / g, which is much higher than the theoretical capacity of graphite materials of 372mAh / g; (2) Due to its high specific surface area, hard carbon materials can provide higher charge and discharge rates, which are suitable for application scenarios that require fast charge and discharge; (3) The raw materials of hard carbon are widely available and relatively low in cost, which is conducive to large-scale production and application. Asphalt is mainly divided into petroleum asphalt and coal asphalt due to different sources and production processes. It has a high carbon atom ratio and is rich in small-sized aromatic molecular compounds. It is composed of aromatic cores and side chains. It is easy to form nearly parallel stacked carbon layers during heating, which is an ideal carbon material precursor for preparing carbon anodes. However, asphalt is easily graphitized during heat treatment, and the prepared carbon material shows a bottleneck problem of low lithium storage specific capacity. Summary of the invention

[0004] The technical problem solved by the present invention is to overcome the problem that the energy density of existing lithium-ion batteries with graphite as negative electrode material is approaching the theoretical limit, and lithium dendrites are easily formed during rapid charging or cycling, resulting in low charging efficiency, and the ideal carbon material precursor asphalt is easily graphitized during heat treatment, and the prepared carbon material exhibits the defect of low lithium storage capacity. Thus, a selenium-sulfur co-doped asphalt-based hard carbon material and a preparation method and application thereof are provided. The selenium-sulfur co-doped asphalt-based hard carbon negative electrode material of the present invention has a high lithium storage capacity and good electrochemical properties, and can be used to prepare negative electrode materials for lithium-ion batteries. The preparation method of the selenium-sulfur co-doped asphalt-based hard carbon material is also simple, economical and environmentally friendly.

[0005] The present invention adopts the following technical solutions to achieve the above purpose:

[0006] The present invention provides a selenium-sulfur co-doped asphalt-based hard carbon material, which is prepared from the following raw materials: the raw materials include: asphalt, a selenium source and a sulfur source.

[0007] In the present invention, the asphalt may be conventional asphalt in the art, preferably one or both of petroleum asphalt and kerosene asphalt, such as petroleum asphalt (purchased from PetroChina).

[0008] In the present invention, the selenium source can be one or more of selenium powder, selenium dioxide and sodium selenite, preferably selenium powder (purchased from Mitsubishi, with a purity of 99.9%) or selenium dioxide (purchased from Maclean, with a purity of 99%), such as selenium powder.

[0009] In the present invention, the sulfur source can be one or more of thiourea (purchased from Aladdin) and sulfur powder (purchased from Maclean, with a purity of 99%), such as thiourea.

[0010] In the present invention, the mass ratio of the asphalt, the selenium source and the sulfur source may be 10-20:1:2, for example 10:1:2.

[0011] In the present invention, the particle size of the selenium-sulfur co-doped asphalt-based hard carbon material may be 4-6 μm, for example, 5 μm.

[0012] The present invention provides a method for preparing a selenium-sulfur co-doped asphalt-based hard carbon material, the preparation method comprising the following steps: (1) mixing asphalt with a selenium source and a sulfur source, and processing the mixture to obtain a solid powder; and (2) carbonizing the solid powder to obtain a selenium-sulfur co-doped asphalt-based hard carbon material.

[0013] In step (1), the asphalt, selenium source and sulfur source are all as described above.

[0014] In step (1), the particle size of the solid powder may be 4-6 μm, for example 4.5 μm.

[0015] In step (1), the asphalt is prepared in advance through a pre-oxidation step.

[0016] In the pre-oxidation step, the asphalt is preferably oxidized under air conditions at about 300° C. for about 3 hours.

[0017] In step (1), the processing includes grinding and screening steps in sequence.

[0018] The grinding time may be a conventional grinding time in the art, such as about 1 hour.

[0019] The screening process can be carried out in a conventional screening device in the art, and the screening device is preferably an air flow screen.

[0020] Wherein, the particle size of the air flow screen is preferably about 200 meshes.

[0021] In step (2), the carbonization is carried out under a protective gas.

[0022] The protective gas may be a conventional protective gas in the art, preferably nitrogen.

[0023] In step (2), the carbonization temperature is preferably programmed.

[0024] The programmed temperature increase is preferably from 25°C to 1150°C.

[0025] Wherein, the programmed heating rate is preferably about 5°C / min.

[0026] The carbonization is preferably carried out at 1150° C. for about 2 hours.

[0027] In step (2), before the solid powder is carbonized, the solid powder can be placed in any container, and the container is preferably a porcelain boat.

[0028] In a preferred embodiment of the present invention, a container containing solid powder is placed in any reaction container, and the reaction container is preferably a tube furnace.

[0029] The present invention provides a negative electrode material, which includes the selenium-sulfur co-doped asphalt-based hard carbon material as described above.

[0030] The present invention provides a method for preparing a negative electrode material, which comprises the following steps: (i) mixing and grinding the selenium-sulfur co-doped asphalt-based hard carbon material as described above with a conductive agent and a binder to obtain a mixture powder; (ii) adding a solvent to the mixture powder to obtain a slurry; (iii) coating the slurry on a metal foil and drying it to obtain a selenium-sulfur co-doped asphalt-based hard carbon negative electrode material.

[0031] In step (i), the conductive agent may be a conventional conductive agent in the art, preferably acetylene black, SuperP, Ketjen black, for example, acetylene black.

[0032] In step (i), the binder may be a conventional binder in the art, preferably polyvinylidene fluoride (PVDF), styrene-butadiene rubber latex (SBR) or carboxymethyl cellulose (CMC), for example, polyvinylidene fluoride (PVDF).

[0033] In step (i), the mass ratio of the selenium-sulfur co-doped asphalt-based hard carbon material, the conductive agent and the binder is preferably 90:5:5.

[0034] In step (ii), the solvent may be a conventional solvent in the art, preferably N-methyl-2-pyrrolidone.

[0035] The mass ratio of the solvent to the mixed powder is preferably 1:1 to 1:1.1, for example, 1:1.05.

[0036] In step (ii), the slurry is preferably a viscous slurry.

[0037] Wherein, the viscosity of the viscous slurry is preferably 3000-4500 centipoise.

[0038] In step (iii), the metal foil may be a conventional metal foil in the art, such as copper foil.

[0039] In step (iii), the drying temperature is preferably about 100°C.

[0040] In step (iii), the drying time is preferably about 12 hours.

[0041] The drying can be carried out in a conventional dryer in the art, and the dryer is preferably an air drier. The present invention removes the solvent in the slurry by an air drier, thereby forming a negative electrode material containing selenium and sulfur co-doped asphalt-based hard carbon material on the surface of the copper foil.

[0042] In step (iii), the slurry is coated on the metal foil using a scraping tool so that the slurry is evenly coated on the metal foil.

[0043] The scraping tool may be a conventional scraping tool in the art, such as a scraper.

[0044] The scraping size of the scraping tool may be a conventional scraping size in the art, for example, 100 μm.

[0045] Wherein, the diameter D50 of the selenium-sulfur co-doped asphalt-based hard carbon negative electrode material is preferably 4-6 μm, for example, 5 μm.

[0046] The present invention also provides a lithium-ion battery, which includes the selenium-sulfur co-doped asphalt-based hard carbon material as described above, wherein the selenium-sulfur co-doped asphalt-based hard carbon material is used as a negative electrode material.

[0047] In the present invention, the operations and conditions of the lithium ion battery preparation method can be conventional operations and conditions in the art.

[0048] In the present invention, the lithium-ion battery further comprises a diaphragm, a positive electrode material and an electrolyte.

[0049] The separator is preferably a polypropylene microporous membrane or a polyethylene microporous membrane, for example, a polypropylene microporous membrane.

[0050] The positive electrode material may be a conventional positive electrode material in the art, preferably lithium.

[0051] Wherein, the electrolyte is preferably lithium hexafluorophosphate (LiPF6) solution.

[0052] In a preferred embodiment of the present invention, the lithium hexafluorophosphate (LiPF6) solution is obtained by mixing lithium hexafluorophosphate and a solvent, and the solvent is preferably a mixture of ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC) and vinylene carbonate (VC).

[0053] Wherein, the volume ratio of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) is preferably 1:1:1.

[0054] Wherein, the content of the vinylene carbonate (VC) preferably accounts for 5% of the total volume of the ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC).

[0055] In a preferred embodiment of the present invention, the concentration of lithium hexafluorophosphate (LiPF6) solution is preferably 0.6-1 mol / L, for example, 1 mol / L.

[0056] In the present invention, it is preferred that the selenium-sulfur co-doped asphalt-based hard carbon material is punched to obtain an electrode sheet.

[0057] Wherein, the diameter of the electrode sheet is preferably 18 mm.

[0058] The shape of the electrode sheet may be a conventional shape in the art, preferably an irregular block, such as a circle.

[0059] In the present invention, the voltage window interval of the lithium-ion battery is preferably 0-2V.

[0060] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0061] The reagents and raw materials used in the present invention are commercially available.

[0062] Furthermore, unless otherwise indicated, all numerical values ​​modified by the term "about" as used herein with respect to amounts of components, reaction conditions, etc., have an error range of ±5%, for example:

[0063] About 300°C means 285°C-315°C. About 3h means 2.85-3.15h. About 1h means 0.95-1.05h. About 2h means 1.9-2.1h. About 5°C / min means 4.75-5.25°C / min.

[0064] The positive and progressive effects of the present invention are:

[0065] (1) The selenium-sulfur co-doped asphalt-based hard carbon material provided by the present invention has a relatively high lithium storage capacity, for example, 343-380 mAh / g.

[0066] (2) The preparation method of the above-mentioned selenium-sulfur co-doped asphalt-based hard carbon material provided by the present invention realizes the co-doping of selenium and sulfur during the carbonization process, thereby suppressing the tendency of asphalt to graphitize during high-temperature carbonization. The preparation method is simple, economical and environmentally friendly.

[0067] (3) The selenium-sulfur co-doped asphalt-based hard carbon material provided by the present invention is used as a negative electrode material for a lithium-ion battery. Since the selenium-sulfur co-doped asphalt-based hard carbon material has good electrochemical properties, the prepared lithium-ion battery also has good electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 XRD patterns of the pitch-based hard carbon materials prepared in Example 1, Comparative Example 1 and Comparative Example 2;

[0069] Figure 2 The first cycle charge and discharge curves of the batteries prepared in Example 1, Comparative Example 1 and Comparative Example 2;

[0070] Figure 3 The first cycle charge and discharge curve of the battery prepared in Example 2;

[0071] Figure 4 The first cycle charge and discharge curve of the battery prepared in Example 3;

[0072] Figure 5 The first cycle charge and discharge curves of the batteries prepared in Comparative Examples 3 and 4;

[0073] Figure 6 This is an EDS element analysis diagram of the SEM test of Comparative Example 4;

[0074] Figure 7 The first cycle charge and discharge curve of the battery prepared in Comparative Example 5;

[0075] Figure 8 This is the first cycle charge and discharge curve of the battery prepared in Comparative Example 6. DETAILED DESCRIPTION

[0076] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0077] Example 1

[0078] 1. Preparation of selenium-sulfur co-doped asphalt-based hard carbon materials:

[0079] Pre-oxidized petroleum asphalt (wherein the pre-oxidation step is to oxidize the petroleum asphalt under air conditions at 300°C for 3h) and selenium powder (purchased from Mitsubishi with a purity of 99.9%) and thiourea (purchased from Aladdin) are mixed, and then ground for 1h and sieved. The sieving is carried out in an air flow sieve with a particle size of 200 meshes to obtain a solid powder with a particle size of 4.5μm. The mass ratio of petroleum asphalt, selenium powder and thiourea is 10:1:2. The obtained solid powder is then placed in a porcelain boat, placed in a tubular furnace, and carbonized under the protection of a nitrogen atmosphere. The temperature is raised from room temperature 25°C to 1150°C and kept at this temperature for 2h, with a heating rate of 5°C / min, to obtain the selenium-sulfur co-doped asphalt-based hard carbon material.

[0080] 2. Preparation of lithium-ion batteries: The selenium-sulfur co-doped asphalt-based hard carbon material, acetylene black and binder PVDF prepared in step 1 are ground in a mortar in a mass ratio of 90:5:5 to obtain a mixture powder, and then N-methyl-2-pyrrolidone is added until the mixture powder is a black viscous slurry, wherein the mass ratio of N-methyl-2-pyrrolidone (purchased from Maiqi Chemical Co., Ltd., purity ≥99.8%) to the mixture powder is 1:1.05. The obtained slurry was evenly coated on a copper foil using a 100 μm scraper, and then the copper foil was vacuum dried at 100 ° C for 12 h to obtain a selenium-sulfur co-doped asphalt-based hard carbon negative electrode material with a particle size D50 of 5 μm, which was then punched into a circular electrode sheet with a diameter of 18 mm, which was the negative electrode of a lithium-ion battery; the obtained electrode sheet was used as the negative electrode, lithium metal as the positive electrode, a polypropylene microporous membrane as the diaphragm, and a 1 mol / L LiPF6 solution as the electrolyte, wherein the LiPF6 solution was composed of a solute LiPF6 and a solvent, wherein the solvent consists of ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC) and vinylene carbonate (VC), wherein the volume ratio of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) is 1:1:1, the content of vinylene carbonate (VC) is 5% of the total volume of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC), and the voltage range is set to 0-2V, so as to prepare a lithium ion battery.

[0081] Example 2

[0082] Except that thiourea was replaced by sulfur powder (purchased from Maclean, with a purity of 99%), the other steps were exactly the same as those in Example 1.

[0083] Example 3

[0084] Except that selenium powder was replaced by selenium dioxide (purchased from Maclean, purity 99%), the other procedures were exactly the same as those in Example 1.

[0085] Comparative Example 1

[0086] 1. Preparation of pure asphalt-based hard carbon materials:

[0087] The same operation as in Example 1 was adopted, except that the raw material was only the pre-oxidized petroleum asphalt used in Example 1, to prepare a pure asphalt-based hard carbon material. 2. Preparation of lithium-ion battery: A lithium-ion battery was prepared by the same steps as in Example 1, except that the particle size D50 of the prepared asphalt-based hard carbon negative electrode material was 9.4 μm.

[0088] Comparative Example 2

[0089] 1. Preparation of selenium-doped asphalt-based hard carbon materials:

[0090] The same operation as in Example 1 is adopted, except that the raw materials are only the pre-oxidized petroleum asphalt and selenium powder used in Example 1, wherein the mass ratio of petroleum asphalt to selenium powder is 10:1, to obtain a selenium-doped asphalt-based hard carbon material.

[0091] 2. Preparation of lithium-ion battery: A lithium-ion battery was prepared by the same steps as in Example 1, except that the particle size D50 of the prepared selenium-doped asphalt-based hard carbon negative electrode material was 5.5 μm.

[0092] Comparative Example 3

[0093] 1. Preparation of nitrogen-doped pitch-based hard carbon materials:

[0094] The same operation as in Example 1 was adopted, except that the raw materials were only the pre-oxidized petroleum asphalt used in Example 1 and melamine, and the mass ratio of petroleum asphalt to melamine was 5:1 to obtain a nitrogen-doped asphalt-based hard carbon material.

[0095] 2. Preparation of lithium-ion battery: A lithium-ion battery was prepared by the same steps as in Example 1, except that the particle size D50 of the prepared nitrogen-doped asphalt-based hard carbon negative electrode material was 5.4 μm.

[0096] Comparative Example 4

[0097] 1. Preparation of nitrogen-sulfur co-doped asphalt-based hard carbon materials:

[0098] The same operation as in Example 1 is adopted, the only difference being that the raw materials are the pre-oxidized petroleum asphalt used in Example 1, as well as melamine and thiourea, wherein the mass ratio of petroleum asphalt, melamine and thiourea is 5:1:1, and a nitrogen-sulfur co-doped asphalt-based hard carbon material is obtained.

[0099] 2. Preparation of lithium-ion battery: A lithium-ion battery was prepared by the same steps as in Example 1, except that the particle size D50 of the prepared nitrogen-sulfur co-doped asphalt-based hard carbon negative electrode material was 5.6 μm.

[0100] Comparative Example 5

[0101] 1. Preparation of boron-doped pitch-based hard carbon materials:

[0102] The same operation as in Example 1 is adopted, the only difference being that the raw materials are the pre-oxidized petroleum asphalt used in Example 1, and boric acid, wherein the mass ratio of petroleum asphalt to boric acid is 5:1 to obtain a boron-doped asphalt-based hard carbon material.

[0103] 2. Preparation of lithium-ion battery: A lithium-ion battery was prepared by the same steps as in Example 1, except that the particle size D50 of the prepared boron-doped asphalt-based hard carbon negative electrode material was 6 μm.

[0104] Comparative Example 6

[0105] Except for petroleum asphalt, the mass ratio of selenium powder to thiourea is 20:1:2; other components, composition and operation are exactly the same as those in Example 1.

[0106] Effect Example 1

[0107] The pitch-based hard carbon materials in Example 1 and Comparative Examples 1-2 were tested by XRD spectra. Figure 1 As shown, Figure 1 The XRD patterns of the pitch-based hard carbon materials prepared in Example 1 and Comparative Examples 1-2 are shown in Table 1. The name and model of the instrument used in the test are: D8 ADVANCE (Bruker, Germany).

[0108] The XRD spectrum of the pitch-based hard carbon material has two broad diffraction peaks at 25° and 43°, which are typical diffraction peaks of hard carbon in the (002) and (100) crystal planes. It can be found that the (002) peak of the pitch-based hard carbon material co-doped with selenium and sulfur becomes wider, indicating that the degree of graphitization of the hard carbon material becomes lower after doping, and more defects are introduced to provide more lithium storage sites. And the (002) peak has a certain shift to the left, indicating that the interlayer spacing of the doped pitch-based hard carbon material has also been improved to a certain extent.

[0109] Effect Example 2

[0110] Comparative Example 4 was subjected to EDS element analysis in SEM testing, and the instrument model was JSX-1000S. Figure 6 As shown, the presence of N and S elements was detected in Comparative Example 4, indicating that nitrogen and sulfur elements were successfully introduced.

[0111] Effect Example 3

[0112] The electrochemical performance of the lithium ion batteries of Examples 1-3 and Comparative Examples 2-6 was tested respectively. Figure 2-5 and Figure 7-8 As shown, and the test results are listed in the following Table 1, the constant current charge and discharge (GCD) test of all batteries adopts CT-4008T test system with a voltage window of 0-2.0V.

[0113] Table 1

[0114] sample Lithium storage capacity mAh / g Example 1 380 Example 2 343 Example 3 356 Comparative Example 1 280 Comparative Example 2 340 Comparative Example 3 254 Comparative Example 4 312 Comparative Example 5 332 Comparative Example 6 330

[0115] It can be seen that compared with the undoped asphalt-based hard carbon material of Example 1, the lithium storage capacity is 280 mAh / g, the lithium storage capacity of Example 2 of the selenium-doped asphalt-based carbon material is 340 mAh / g, the lithium storage capacity of Example 3 of the nitrogen-doped asphalt-based hard carbon material is 254 mAh / g, the lithium storage capacity of Example 4 of the nitrogen-sulfur co-doped asphalt-based hard carbon material is 312 mAh / g, the lithium storage capacity of Example 5 of the boron-doped asphalt-based hard carbon material is 332 mAh / g, and the lithium storage capacity of Example 6 of the selenium- and sulfur-co-doped asphalt-based hard carbon material having a mass ratio of petroleum asphalt, selenium powder and thiourea different from that of the present application is 330 mAh / g. It can be seen that the lithium storage capacity of Examples 1-3 of the present application including selenium-sulfur co-doped asphalt-based carbon materials is significantly improved, and its lithium storage capacity is 343-380 mAh / g, especially the lithium storage capacity of Example 1 is as high as 380 mAh / g.

Claims

1. A selenium-sulfur co-doped pitch-based hard carbon material, characterized in that: The invention is prepared from the following raw materials, which include asphalt, a selenium source and a sulfur source.

2. The selenium-sulfur co-doped pitch-based hard carbon material according to claim 1, characterized in that: The mass ratio of the asphalt, the selenium source and the sulfur source is 10-20:1:2, for example 10:1:

2.

3. The selenium-sulfur co-doped asphalt-based hard carbon material according to claim 1, characterized in that: It meets one or more of the following conditions: (1) The selenium source is one or more of selenium powder, selenium dioxide and sodium selenite, preferably selenium powder or selenium dioxide, such as selenium powder; (2) The sulfur source is one or more of thiourea and sulfur powder, such as thiourea; (3) The asphalt is one or both of petroleum asphalt and kerosene asphalt, for example, petroleum asphalt; (4) The particle size of the selenium-sulfur co-doped asphalt-based hard carbon material is 4-6 μm, for example, 5 μm.

4. A method for preparing a selenium-sulfur co-doped pitch-based hard carbon material as claimed in any one of claims 1 to 3, characterized in that: It includes the following steps: (1) mixing asphalt with a selenium source and a sulfur source, and processing the mixture to obtain a solid powder; and (2) carbonizing the solid powder to obtain a selenium-sulfur co-doped asphalt-based hard carbon material.

5. The method for preparing a selenium-sulfur co-doped pitch-based hard carbon material according to claim 4, characterized in that: It meets one or more of the following conditions: (1) The particle size of the solid powder is 4-6 μm, for example 4.5 μm; (2) In step (1), the asphalt is prepared in advance by a pre-oxidation step; Preferably, the pre-oxidation step is oxidation in air at about 300° C. for about 3 h; (3) In step (1), the processing includes grinding and screening steps in sequence; Preferably, the grinding process takes about 1 hour; Preferably, the screening device is an airflow screen; Wherein, the particle size of the airflow sieve is about 200 mesh; (4) In step (2), the carbonization is carried out under a protective gas; Wherein, the protective gas is preferably nitrogen; (5) In step (2), the carbonization includes programmed temperature increase; Preferably, the programmed temperature is increased from 25°C to 1150°C; Preferably, the temperature program is maintained at 1150° C. for about 2 hours; Preferably, the heating rate of the programmed temperature is about 5°C / min; (6) In step (2), before carbonizing the solid powder, the solid powder is placed in a container, such as a porcelain boat; Therein, a container containing solid powder is placed in a reaction container, such as a tube furnace.

6. A negative electrode material, characterized in that It comprises the selenium-sulfur co-doped asphalt-based hard carbon material as described in any one of claims 1 to 3.

7. A method for preparing a negative electrode material, characterized in that: It includes the following steps: (i) mixing and grinding the selenium-sulfur co-doped asphalt-based hard carbon material as described in any one of claims 1 to 3 with a conductive agent and a binder to obtain a mixture powder; (ii) adding a solvent to the mixture powder to obtain a slurry; (iii) coating the slurry on a metal foil and drying it to obtain a selenium-sulfur co-doped asphalt-based hard carbon negative electrode material.

8. The method for preparing the negative electrode material according to claim 7, characterized in that: It meets one or more of the following conditions: (1) The mass ratio of the selenium-sulfur co-doped asphalt-based hard carbon material, the conductive agent and the binder is preferably 90:5:5; (2) The conductive agent is acetylene black, SuperP, Ketjen black, for example, acetylene black; (3) The binder is polyvinylidene fluoride, styrene-butadiene rubber latex or carboxymethyl cellulose, for example, polyvinylidene fluoride; (3) The solvent is N-methyl-2-pyrrolidone; (4) The mass ratio of the solvent to the mixed powder is 1:1 to 1:1.1, for example, 1:1.05; (5) The slurry is a viscous slurry; Wherein, the viscosity of the viscous slurry is 3000-4500 centipoise; (6) The metal foil is copper foil; (7) In step (iii), the drying temperature is 100° C.; (8) In step (iii), the drying time is 12 hours; (9) In step (iii), the drying is carried out in a dryer, and the dryer is preferably a forced air dryer; (10) In step (iii), the slurry is coated on a metal foil using a scraping tool; Wherein, the scraping tool is a scraper; Wherein, the scraping size of the scraping tool is 100 μm; (11) The diameter D50 of the selenium-sulfur co-doped asphalt-based hard carbon negative electrode material is 4-6 μm, for example, 5 μm.

9. A lithium ion battery, characterized in that: The invention comprises the selenium-sulfur co-doped asphalt-based hard carbon material as described in any one of claims 1 to 3, a separator, a positive electrode material and an electrolyte.

10. The lithium ion battery according to claim 9, characterized in that: It meets one or more of the following conditions: (1) The separator is a polypropylene microporous membrane or a polyethylene microporous membrane, for example, a polypropylene microporous membrane; (2) The positive electrode material is lithium; (3) The electrolyte is a lithium hexafluorophosphate solution; Wherein, the lithium hexafluorophosphate solution is obtained by mixing lithium hexafluorophosphate and a solvent, and the solvent is preferably a mixture of ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate and vinylene carbonate; Wherein, the volume ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is preferably 1:1:1; Wherein, the content of the vinylene carbonate preferably accounts for 5% of the total volume of the vinyl carbonate, dimethyl carbonate and ethyl methyl carbonate; Wherein, the concentration of the lithium hexafluorophosphate solution is preferably 0.6-1 mol / L, for example, 1 mol / L; (4) stamping the selenium-sulfur co-doped asphalt-based hard carbon material to obtain an electrode sheet; Wherein, the diameter of the electrode sheet is preferably 18 mm; Wherein, the shape of the electrode sheet is preferably an irregular block, for example, a circle; (5) The voltage window range of the lithium-ion battery is 0–2V.

Citation Information

Patent Citations

  • Sulfur / selenium bridge asphalt porous polymer and preparation method thereof

    CN113058570A

  • Preparation method of hard carbon negative electrode material for sodium ion battery

    CN117810446A

  • Asphalt resin-based hard carbon composite material as well as preparation method and application thereof

    CN117894980A

  • Preparation method and application of heteroatom doped asphalt-based hard carbon

    CN119100369A

  • Preparation method for lithium-enriched solvent-philic lithium ion battery positive electrode material

    WO2024051186A1